Perancangan User experience Aplikasi BAZNAS Jombang berbasis Mobile menggunakan Metode Design Thinking (Studi Kasus : BAZNAS Jombang) - Ananda Risqi Amalia; Intan Sartika Eris Maghfiroh; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Badan Amil Zakat Nasional Kabupaten Jombang (BAZNAS) is an agency that has the duties and functions of collecting and distributing zakat, infaq, and alms (ZIS) at the Jombang Regency level. Based on the observations and the results of pre-research interviews, it is known that BAZNAS Jombang requires a mobile application that can support all work programs and meet user needs. These needs include a system for calculating the amount of zakat, paying zakat (either by bank transfer, direct meeting, or QRIS code), online infaq, donations, news, zakat literacy, and consultation. This research aims to meet user needs and solve problems experienced by users when donating through a mobile application. The design method used is design thinking and usability testing methods for testing prototypes. The design thinking method consists of 5 stages: empathize, define, ideate, prototype, and test. The data collection results using the In-depth Interview method found 6 problems that must be resolved and 14 needs which include payment processes, donations and zakat, as well as transparency of funds. Of all these problems and needs, produce 4 menus and 111 pages with guidelines using google material design. Based on the results of the final prototype evaluation of the 10 scenarios tested on 5 users using the moderated usability testing method through the Maze, it is known that all users have completed the scenarios given with an average success rate of 100% from the direct and indirect path. Meanwhile, through the calculation of the Likert scale, an average value of 4.82 is obtained. Even so, 11 pages had to be Redesigned because they were considered different from users' needs, expectations and perceptions.